ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, LOKASI, DAN PROMOSI TERHADAP MINAT BELI IKAN SEGAR DI TPI WONOKERTO KABUPATEN PEKALONGAN - Nisbatul Khasanah; Rini Hidayah (MANAJEMEN DEWANTARA, 2026)
This research is motivated by the importance of understanding the factors influencing consumer purchasing interest in fresh fish at the Wonokerto Fish Auction Place (TPI) in Pekalongan Regency. This study aims to analyze the influence of price perceptions, product quality, location, and promotion on consumer purchasing interest in fresh fish at the Wonokerto TPI. This study used a quantitative approach with a survey method by distributing questionnaires to 105 respondents, who were fresh fish consumers at the Wonokerto TPI. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that perceptions of price, location, and promotion had a positive and significant effect on consumer purchasing interest, while product quality had no significant effect. The R-square value of 0.602 indicates that the research variables can explain 60.2% of consumer purchasing interest. These results indicate that pricing strategy, location accessibility, and promotion are important factors in increasing consumer purchasing interest in fresh fish at the Wonokerto TPI.